Analisis Hambatan Pemenuhan Bukti Setoran Pph Final sebagai Persyaratan Balik Nama Sertifikat Tanah di Kantor Pertanahan Kota Bandar Lampung - Rani Cahyati; Ratna Septiyanti (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study analyzes the obstacles in fulfilling the proof of deposit for Final Income Tax (PPh Final) as a requirement for land certificate name transfer at the Land Office of Bandar Lampung City. These obstacles impact legal uncertainty regarding land ownership and slow down public services. The research employs a descriptive analytical method with a qualitative approach. Data were collected through in-depth interviews with counter officers, verifiers, and the Land Rights Determination and Registration section, as well as direct observation and documentation at the local office. The findings identify three main classifications of obstacles. First, technical obstacles include payment data not being readable in the Land Office Computerization System (KKP) and barcodes on tax clearance certificates being unreadable. Second, administrative obstacles encompass data mismatches (nominal amounts, identities, Tax Object Numbers) and incomplete documents. Third, document-related obstacles include poor-quality photocopies and discrepancies in tax dates or years. Contributing factors are data entry errors (human error), lack of thoroughness, integration issues between the KKP system and the tax system, as well as taxpayers' low technical understanding. The consequences include process delays, re-verification with the tax office, and document returns. This study concludes that system-related obstacles, particularly the lack of optimal integration, are dominant. Recommended improvements include integrating the KKP system with the Directorate General of Taxes, enhancing automatic validation, simplifying validation procedures at the tax office, and increasing tax literacy among taxpayers.